Upland rice cultivar responses to row spacing and water stress across multiple environments - Heinemann, Alexandre B.; Ramírez Villegas, Julián Armando; Nascente, Adriano; Zeviani, Walmes Marques; Stone, Luís Fernando; Sentelhas, Paulo Cesar (Cambridge University Press, 2017)
Upland rice (Oryza sativa L., UR) could be an option under soybean–maize crop rotation system. However, the recommended row spacing for UR (0.30 m) is shorter than that recommended for soybean and corn (0.40 m), limiting the use of UR in this rotation. We hypothesize that cultivar adaptation to wider than recommended row spacing and local environmental conditions harbour significant potential for overcoming the yield constraints of wider row spacing. We evaluated the row spacing effects on rice grain yield and their components in UR cultivars grown under different water deficit conditions. The experiments were designed as a randomized block in a split–split-plot scheme with sites (the cities of Santo Antônio de Goiás, Porangatu and Formoso) as main plots, row spacing (0.25, 0.35, 0.45 and 0.55 m) as the subplots and UR cultivars (one old and two modern genotypes) as the sub-subplots. We found that, in the less stressful environments, the modern cultivars, BRSMG Curinga and BRS Primavera, presented the highest grain yield. By contrast, in environments with moderate to intense water stress, the traditional cultivar, Douradão, presented the best performance, regardless of row spacing used. We conclude that UR is a viable option for soybean–maize rotation systems, as the UR cultivars tested presented no noticeable yield losses when sown with the same row spacing used for soybean and maize crops (0.40 m). In terms of impact, it can lead to an increase in UR cropped area in Brazil, and decrease in dependence on flooded rice harvested in the south of the country.